2021
DOI: 10.3390/su132413573
|View full text |Cite
|
Sign up to set email alerts
|

Fostering University Students’ Engagement in Teamwork and Innovation Behaviors through Game-Based Learning (GBL)

Abstract: Higher Education Instituions (HEIs) should be the driving force behind the training of college students in terms of both hard and soft skills (for example, innovation and teamwork competencies), and they should also do so without neglecting their health and well-being, perhaps more than ever in these complex times of the SARS-CoV2 pandemic. Game-based learning (GBL) could be a powerful and useful tool in this regard. There is, however, some controversy surrounding the use of games for learning purposes in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 92 publications
(173 reference statements)
2
9
0
1
Order By: Relevance
“…Secondly, consistent with the studies of negative outcomes of affective conflict [ 3 , 7 , 36 , 37 ], the results indicated that affective conflict was negatively correlated with students’ innovative competence. Affective conflict results in discussion that is off-topic for class content, and it evokes negative emotions and amplifies aggression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Secondly, consistent with the studies of negative outcomes of affective conflict [ 3 , 7 , 36 , 37 ], the results indicated that affective conflict was negatively correlated with students’ innovative competence. Affective conflict results in discussion that is off-topic for class content, and it evokes negative emotions and amplifies aggression.…”
Section: Discussionsupporting
confidence: 87%
“…Students’ innovation competence has been identified as an important learning goal at the university level [ 1 , 2 ]. How to improve students’ innovative competence is emphasized and debated in university pedagogy [ 2 , 3 ]. Innovation is “the intentional introduction and execution within a group or organization of ideas, processes, products or procedures, new to the relevant unit of adoption, designed to significantly benefit the individual, the group, the organization or wider society” [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several research projects conducted worldwide regarding online teaching and learning, particularly after the outbreak of the COVID-19 pandemic [6,8,26,[28][29][30][31][32][33][34][35][36]. However, most of these research papers are based on quantitative studies, particularly on survey of students.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 99%
“…Meanwhile in organizations that implement TQM, teamwork, partnerships, and relationships are established and fostered, both between school members and students, government institutions, and the surrounding community (Martín-Hernández et al, 2021).…”
Section: Teamworkmentioning
confidence: 99%